2021
DOI: 10.3389/fbuil.2021.688484
|View full text |Cite
|
Sign up to set email alerts
|

Remote Working in the COVID-19 Pandemic: Results From a Questionnaire on the Perceived Noise Annoyance

Abstract: Noisiness in the working environment was largely proved to have effects on the working activity and performance. To limit the spreading of the COVID-19 pandemic in the first wave between March and May 2020, Italian workers had massively started performing remote working. Insights on the subjective perception of noise annoyance under the remote working settings were thus necessary. Workers from a university and from several large and small Italian companies, resulting in 1,934 participants overall, answered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The concentration of more people in the domestic environment led to overcrowding issues and related noise exposure that negatively impacted WFH. House-related noise annoyance increased compared to pre-pandemic period ( Şentop Dümen and Şaher, 2020 ), becoming the main source of disruption whilst WFH, proportional to the number of persons present at home ( Puglisi et al, 2021 ; Torresin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of more people in the domestic environment led to overcrowding issues and related noise exposure that negatively impacted WFH. House-related noise annoyance increased compared to pre-pandemic period ( Şentop Dümen and Şaher, 2020 ), becoming the main source of disruption whilst WFH, proportional to the number of persons present at home ( Puglisi et al, 2021 ; Torresin et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the measures taken with the health emergency, the COVID-19 lockdown represented an unprecedented scenario in terms of outdoor noise levels reduction and concentration of activities in the domestic space ( You et al, 2022 ). Several surveys have addressed the impact of the acoustic environment on building occupants ( Şentop Dümen and Şaher, 2020 ; Andargie et al, 2021 ; Bartalucci et al, 2021 ; Caniato et al, 2021 ; Dzhambov et al, 2021 ; Lee and Jeong, 2021 ; Puglisi et al, 2021 ; Aumond et al, 2022 ). The focus has been more often on noise annoyance, perceived loudness, salience of specific noise sources, general evaluation of the acoustic environment (i.e., sound quality and appropriateness) and perceived magnitude of (negative) impacts of noise exposure, sometimes comparing the ratings collected during lockdown to those prior to lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…This factor was addressed by Puglisi et al [17]. Through an online questionnaire on perceived noise in the workplace, with a total of 1,934 respondents also from Italy, they concluded that noise nuisance, which occurs mainly in employees working in the same room with other members of the household, has a negative effect on concentration, attention, or relaxation [17]. These effects can be considered as disadvantages of working from home and therefore noise is one of the possible negatives of the home office.…”
Section: Literary Researchmentioning
confidence: 98%
“…One of the unusual aspects that affect employee satisfaction and productivity when working from home during a pandemic is also noise. This factor was addressed by Puglisi et al [17]. Through an online questionnaire on perceived noise in the workplace, with a total of 1,934 respondents also from Italy, they concluded that noise nuisance, which occurs mainly in employees working in the same room with other members of the household, has a negative effect on concentration, attention, or relaxation [17].…”
Section: Literary Researchmentioning
confidence: 99%
“…These factors are also frequently mentioned as sources of dissatisfaction and stress ( Wineman & Barnes, 2018 ). At home, such sources of noise are less frequently experienced, although different noise sources, such as noise from doorbells, conversations between household members, sounds from television, outdoor construction works and road traffic, can all affect concentration and well-being ( Puglisi et al, 2021 ), ( Torresin et al, 2021 ). The limited research on WFH also shows that employees who have a dedicated workroom with ergonomic furniture developed fewer mental health issues ( Xiao et al, 2021 ), and rated their productivity more positively ( Awada et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%